Jewish schools rather than Jewish education? School choice and community dynamics in multicultural society. (12th February 2020) - Samson, Maxim G. M.
Abstract: The expansion of faith schooling in countries such as England raises important questions about their appeal in multicultural societies. Through a case study approach, this article aims to understand the influences behind parents' decisions to send their children to Jewish schools. It illustrates a tension experienced by Jewish parents between a desire for their children to be educated as a community of 'similar' peers, and the segregation that might result as a consequence. In order to 'justify' their choice of separate schooling, parents constructed a desirable, essentialized notion of Jewishness that coalesced their two main selection criteria, academic standards and the presence of other Jewish students. By operationalizing their Jewishness for 'secular' purposes in such a way, they were able to secure a perceived superior academic education whilst avoiding disfavoured 'others' in multicultural comprehensive schools, and in the process defined multiculturalism on their own terms. Consequently, the article foregrounds the broader dynamics of multiculturalism and community that are implicated in questions of (faith) school choice, and the complex intertwinement of parents' school selection criteria.